LAMINAR FLOW THROUGH A TUBE WITH AN EASILY PENETRABLE ROUGHNESS NEAR AXIS - Гаєв, Є.О. (Proceedings of National Aviation University (archive), 2012)
Mathematical model has been suggested and investigation carried out of laminar flow through a round tube with a porous insertion (easily penetrable roughness, EPR) in its middle along the axis. Velocity and shear fields have been found analytically for stable flow region, as well as hydraulic resistance as functions of EPR density and its height.